Strategy for Zakat Collection and Distribution in the Sembako Distribution Program at The Covid-19 Pandemic Time at the National Amil Zakat Agency (BAZNAS) South Sumatra Province - Sari, Kiki Purnama; Saprida, Saprida; Muharir, Muharir (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
This thesis discusses the strategy for the collection and distribution of zakat programs in distributing The Basic Food during the Covid-19 pandemic at the National Amil Zakat Agency (BAZNAS) of South Sumatra Province. This study aims to determine the strategy program for the collection and distribution of zakat programs in distributing The Basic Food during the Covid-19 pandemic at the National Amil Zakat Agency (BAZNAS) of South Sumatra Province. This research used a descriptive qualitative method. Data collection techniques used the method of observation, interviews, and documentation. Meanwhile, the data analysis technique used data reduction, data presentation, and conclusion drawing. The results of the research conducted indicated that (1) the collection strategies carried out by BAZNAS of South Sumatra Province were: socialization, collecting UPZ (Zakat Collection Unit), digital fundraising, and collaborating with banks. (2) The distribution of zakat in the food distribution program during the covid-19 pandemic at the National Zakat Amil Agency (BAZNAS) of South Sumatra Province, through the Smart Sumsel, Care Sumsel, Healthy Sumsel, Taqwa Sumsel, Prosperous Sumsel programs. (3) The food distribution program during the covid-19 pandemic at the National Zakat Amil Agency (BAZNAS) of South Sumatra Province followed the covid-19 handling protocol. Therefore, the distribution of The Basic Food was carried out without violating the covid-19 pandemic handling protocol. ***Penelitian ini membahas strategi penghimpunan dan penyaluran zakat dalam Program Sebar Sembako Pada Masa Pandemi Covid-19 di Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Selatan. Penelitian bertujuan untuk mengetahui Strategi Penghimpunan dan Penyaluran Zakat Dalam Program Sebar Sembako Pada Masa Pandemi Covid-19 di Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Selatan. Metode penelitian ini dengan menggunakan metode kualitatif deskriptif. Teknik pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Sedangkan teknik analisis data menggunakan reduksi data, penyajian data, penarikan kesimpulan. Hasil penelitian yang dilakukan menunjukkan bahwa (1) Strategi penghimpunan yang di lakukan BAZNAS Provinsi Sumatera Selatan yaitu: sosialisasi, mengumpulkan UPZ (Unit Pengumpulan Zakat), fundraising digital, dan bekerja sama dengan bank. (2) Penyaluran zakat dalam program sebar sembako pada masa pandemi covid-19 di Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Selatan yaitu melalui program sumsel cerdas, sumsel peduli, sumsel sehat, sumsel taqwa, sumsel makmur. (3) Program sebar sembako pada masa pandemi covid-19 di Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Selatan yaitu mengikuti protokol penanganan covid-19, oleh karena itu pembagian paket sembako dilakukan dengan tidak melanggar protokol penanganan pandemi covid-19.Keywords: Collection Strategy, Distribution Strategy, Food Distribution Program.